2018
DOI: 10.1155/2018/4238435
|View full text |Cite
|
Sign up to set email alerts
|

Host-Parasite Interactions in Individuals with Type 1 and 2 Diabetes Result in Higher Frequency ofAscaris lumbricoidesandGiardia lambliain Type 2 Diabetic Individuals

Abstract: Host-parasite interactions in diabetic patients might influence diabetes complications and intestinal parasitosis. The aim was to investigate the occurrence of enteroparasites in individuals with diabetes types 1 and 2. A descriptive study was designed to estimate frequencies of parasites and to compare them in individuals with diabetes types 1 and 2 from two Health Centers and one hospital in the Federal District of Brazil. Patients were allocated to the study by convenience. Three fecal samples of 156 diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 26 publications
(24 reference statements)
1
16
1
2
Order By: Relevance
“…In contrast, some scholars [ 39 , 40 ] found that diabetes mellitus (T1DM + T2DM) patients have a lower probability of intestinal parasitosis. Previously, Akinbo FO et al [ 35 ] and Machado ER et al [ 41 ] studies stated that the frequency of IPIs is lower in T1DM compared to T2DM individuals, which are of potential interest in the interpretation of the findings of Tangi FB et al [ 39 ] and Nazligul Y et al studies [ 40 ]. The variation between our findings and other studies outcomes may be attributed to differences in sample size; study population, area, and season; detected parasites; and diabetic management protocol, which are known confounding factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, some scholars [ 39 , 40 ] found that diabetes mellitus (T1DM + T2DM) patients have a lower probability of intestinal parasitosis. Previously, Akinbo FO et al [ 35 ] and Machado ER et al [ 41 ] studies stated that the frequency of IPIs is lower in T1DM compared to T2DM individuals, which are of potential interest in the interpretation of the findings of Tangi FB et al [ 39 ] and Nazligul Y et al studies [ 40 ]. The variation between our findings and other studies outcomes may be attributed to differences in sample size; study population, area, and season; detected parasites; and diabetic management protocol, which are known confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, S. haematobium , S. mansoni , H. nana , Cryptosporidium spp., and E. histolytica compromised the identified parasites, with considerably higher prevalences in diabetic individuals. Notably, those parasites are commonly detected in diabetic patients [ 33 41 ]. The previous studies were also reported a high frequency of H. nana, Cryptosporidium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence about the relationship between pathophysiological mechanisms of diabetes and COVID-19 are limited and further research is still needed. (280,282,283), and Giardia lamblia (283). Interestingly, diabetic patients who were treated with metformin had less P. falciparum infections compared to untreated patients (276).…”
Section: Coronaviruses (Cov)mentioning
confidence: 98%
“…Patients with T2DM have an elevated risk of infection with Plasmodium falciparum ( 276 ), Toxoplasma gondii ( 277 ), Opisthorchis viverrini ( 278 ), Strongyloides stercoralis ( 279 ), Cryptosporidium parvum ( 280 ), Blastocystis hominis ( 281 ), Ascaris lumbricoides ( 280 , 282 , 283 ), and Giardia lamblia ( 283 ). Interestingly, diabetic patients who were treated with metformin had less P. falciparum infections compared to untreated patients ( 276 ).…”
Section: Effects Of T2dm On the Susceptibility Of Patients To Infectimentioning
confidence: 99%
“…A few studies of parasitic infection among people with diabetes have been reported to date [6]. These studies suggest that DM is significantly associated with the prevalence of intestinal parasites or common intestinal parasites, such as Ascaris lumbricoides, Entamoeba histolytica, Giardia duodenalis, and Opisthorchis viverrini [7][8][9]. Thailand has a rapidly increasing prevalence of type 2 DM (T2DM) [10,11].…”
Section: Introductionmentioning
confidence: 99%